Fünfter Gentechnologiebericht Sachstand und Perspektiven für Forschung und Anwendung - Fehse, Boris; Hucho, Ferdinand; Bartfeld, Sina; Clemens, Stephan; Erb, Tobias; Fangerau, Heiner; Hampel, Jürgen; Korte, Martin; Marx-Stölting, Lilian; Mundlos, Stefan; Osterheider, Angela; Pichl, Anja; et al. (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
In the 'Fifth Gene Technology Report', renowned experts provide an overview of current developments and their applications in the dynamically evolving research field of gene and biotechnologies. They examine, among other topics, genetic diagnostics, somatic gene therapy, the development of vaccines, stem cell and organoid research, green gene technology, synthetic biology, gene drives, genome editing, epigenetics and single cell analysis. In addition to reporting on the current state of affairs in this field, the authors also discuss society's perception of gene technologies and ethical and legal issues relating to them, such as genome edit-ing, cerebral organoids and big data in personalised medicine. Moreover, the interdisciplinary task force 'Gentechnologiebericht' (Gene Technology Report) offers recommendations on action that could be taken in relation to the key issues. With contributions by Karla Alex, Sina Bartfeld, Meik Bittkowski, Inge Broer, Lorina Buhr, Stephan Clemens, Wolfgang Van den Daele, Hans-Georg Dederer, Tobias J. Erb, Nina Gasparoni, Heiner Fangerau, Boris Fehse, Jürgen Hampel, Louise Herde, Ferdinand Hucho, Ali Jawaid, Aida Khachatryan, Sarah Kohler, Alma Kolleck, Martin Korte, Cordula Kropp, Alfons Labisch, Markus Lehmkuhl, Melanie Leidecker-Sandmann, Annette Leßmöllmann, Isabelle M. Mansuy, Lilian Marx-Stölting, Andreas Merk, Yannick Milhahn, Fruzsina Molnár-Gábor, Stefan Mundlos, Staffan Müller-Wille, Angela Osterheider, Anja Pichl, Barbara Prainsack, Jens Reich, Marlen Reinschke, Ortwin Renn, Hans-Jörg Rheinberger, Arnold Sauter, Hannah Schickl, Silke Schicktanz, Volker Stollorz, Constanze Störk-Biber, Jochen Taupitz, Jörn Walter, Eva C. Winkler, Martin Zenke and Michael M. Zwick.